Integrating Information System Success Model (ISSM) And Technology Acceptance Model (TAM): Proposing Students’ Satisfaction with University Web Portal Model - Ismail Olatunji Adeyemi; Abdulwahab Olanrewaju Issa (Record and Library Journal, 2020)
Background of the study: The web portal is a tool that has been adopted by universities to manage data and information of students and faculty. The portal is an information system as it is driven by information.